Are there relationships among quality of work life, organizational commitment and organizational entrenchment? - Milhome, Jaqueline Cavalcante; Rowe, Diva Ester Okazaki; Dos-Santos, Marcos Gilberto (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
Employees influence substantially the organizational outcomes. Their point of view about some organizational elements may influence, and also be influenced by, their kind of links developed to the organization. Within that context, this research aims to analyze the possible relationships between quality of work life, organizational commitment and organizational entrenchment. With that in view, an explanatory, quantitative research was carried out that used a survey composed of three validated scales, each related to one of the examined constructs. The sample was 187 employees and the data were analyzed by means of multiple regression.. The results confirmed some hypotheses and contributed to reflex about both how important the link developed by the worker to the organization is and how the kinds of link can play a role with respect to employees’ perception about organizational practices and positions.